2011
DOI: 10.1371/journal.pone.0021005
|View full text |Cite|
|
Sign up to set email alerts
|

An Improved Transplantation Strategy for Mouse Mesenchymal Stem Cells in an Acute Myocardial Infarction Model

Abstract: To develop an effective therapeutic strategy for cardiac regeneration using bone marrow mesenchymal stem cells (BM-MSCs), the primary mouse BM-MSCs (1st BM-MSCs) and 5th passage BM-MSCs from β-galactosidase transgenic mice were respectively intramyocardially transplanted into the acute myocardial infarction (AMI) model of wild type mice. At the 6th week, animals/tissues from the 1st BM-MSCs group, the 5th passage BM-MSCs group, control group were examined. Our results revealed that, compared to the 5th passage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 47 publications
0
53
0
1
Order By: Relevance
“…Some studies showed that the capability of MSC differentiation reduced gradually after passaged [5,20]. It also had been found that PR-MSCs improved cardiac function in mice with myocardial infarction (MI) [6,21]. But it was difficult to obtain sufficient PR-MSCs in clinical application [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the capability of MSC differentiation reduced gradually after passaged [5,20]. It also had been found that PR-MSCs improved cardiac function in mice with myocardial infarction (MI) [6,21]. But it was difficult to obtain sufficient PR-MSCs in clinical application [22].…”
Section: Discussionmentioning
confidence: 99%
“…Doubtlessly this would be of great assistance in replacing large zonal areas of damaged cardiomyocytes within the heart. Having said this, recently mouse bone marrow mesenchymal stem cells have been experimentally transplanted into an acute damage heart model [38]. Interestingly, primary mesenchymal stem cells fared much better at cardiac regeneration than passaged stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also problems occur with respect to limited stem cell survival upon their implantation into areas of damaged heart tissue due limiting survival as outlined above (35). Curiously too, stem cell manipulations are technique sensitive in that primary harvested mesenchymal stem cells are better equipped to be employed in cardiac regeneration than stem cells that have been passaged ex vivo as described in the previous section [38]. These negative points serve to indicate that working with stem cells is by no means predictable or technically straightforward.…”
Section: Downsides Of Stem Cell Therapymentioning
confidence: 99%
“…23 The finding that other stem cell populations, like bone marrow derived stem cells and mesenchymal stem cells can differentiate into cardiomyocytes has prompted studies on the influence of these cells when directly injected into a defunct rat myocardium and were found to increase the functionality of the left ventricle post-MI. 24,25 There have been many cell injection therapy clinical trials in the past few years using, e.g. different stem cells, and smooth muscle cells.…”
Section: 18mentioning
confidence: 99%